CENTURY AGREEMENT: A TURNİNG POİNT İN AZERBAİJAN’S ENERGY POLİCY - Zargarova Ellada Khairullah (Foundations and Trends in Research, 2025)
The article titled "The Century Agreement: A Turning Point in Azerbaijan’s Energy Policy" discusses the significance of the Contract of the Century signed in 1994 between Azerbaijan and a consortium of international oil companies. This agreement marked a pivotal moment in Azerbaijan’s energy policy, as it opened the country’s oil sector to foreign investment and technological expertise, and it provided a roadmap for Azerbaijan to become a key player in the global energy market. The article highlights how this agreement led to major infrastructural projects, such as the Baku-Tbilisi-Ceyhan (BTC) pipeline, and how it contributed to the economic and political stabilization of the country. The Contract of the Century also helped Azerbaijan strengthen its relations with Western countries and attracted foreign investments, boosting the country’s economic growth and transforming its energy sector into a significant regional force. In essence, the article underscores the importance of the Contract of the Century in shaping Azerbaijan’s energy policies, positioning the country as a central hub in the energy corridor connecting Europe and Asia.